Thermal studies on chromium(II) salts: part 2 - Crouse, Karen Anne; Badri, M.; Wong, Tian Baw (Elsevier Science, 1998)
The thermal behavior of Cr(pn)3Br2·2H2O, Cr(pn)3Cl2·2H2O, Cr(pn)3SO4, Cr(dien)2Br2, Cr(dien)2Cl2, Cr(dien)Cl2 and Cr(dien)Br2 was investigated using TG and DSC under nitrogen atmosphere. The thermograms are interpreted and the enthalpies of dissociation are calculated where possible.